Optimizing cycling postures: Upper limb muscle effort and aerodynamic performance - Li, X.; Zhou, P.; Zhang, X. (International Journal of Sports Physiology and Performance, 2026)
Purpose: Prior cycling research has primarily investigated lower limb muscle activation, biomechanical power output, and aerodynamic drag, often overlooking upper limb functions, posture-specific fatigue, and applicability to amateurs. This study examines the relationship between aerodynamic drag and upper limb muscle activity to identify optimal cycling postures balancing aerodynamic efficiency and physiological demands.